TOC INDONESIAN JOURNAL OF LEGAL AND FORENSIC SCIENCE VOLUME 6, TAHUN 2016 - Wirasuta, gelgel (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2016)
INDONESIAN JOURNAL OF LEGAL AND FORENSIC SCIENCE VOLUME 6, TAHUN 2016